Estudo fitoquímico e investigação da atividade citotóxica das folhas e cascas do caule de Guatteria pogonopus (Annonaceae) - Santos, Maria de Fátima Costa (2015)
This paper presents the results obtained of the phytochemical bioguide of methanol extracts of the leaves and stem bark of Guatteria pogonopus Mart., a species belonging to the family Annonaceae. The botanical material (leaves and stem bark) were collected in the National Park Serra de Itabaiana (PARNA), Sergipe, Brazil. The extracts were obtained by maceration method at room temperature initially with hexane and then methanol, resulting in the hexane (EHF e EHC) and methanol (EMF e EMC) extracts, respectively. The methanol extracts from the leaves (EMF) and stem bark (EMC) indicated the presence of alkaloids when the Dragendorff reagent was applied that was submitted to the acid-base treatment resulting in the chloroform fractions alkaloid (FCAF and FCAC), and neutral fractions (FCNF and FCNC), respectively. The alkaloid fractions (FCAF and FCAC) were then subjected to the usual chromatographic techniques allowing the isolation of alkaloids. The FCAF fraction resulted in the isolation of six alkaloids identified as: lysicamine, (S)-(+)-nuciferine, (S)-(+)-roemerine, (-)- tetrahydropseudocolumbamine, (S)-(+)-isocoridine and a mixture of govanine, liriodenine and lysicamine. The FCAC fraction led to the identification of ten different mixtures alkaloids, such as puterine, anonaine, nornuciferine, obovanine, isopiline, Omethylisopiline, launobine, oxoputerine, liriodenine and lanuginosine. The alkaloids were identified through the techniques of MS and NMR 1H and 13C 1D and 2D as well as, comparison to literature data. Furthermore, the pure alkaloids isolated from the leaves were submitted the specific optical rotation measures. The extracts, fractions, pure alkaloids and in the mixture were subjected to evaluation of the cytotoxic activity by the Alamar Blue method, which observed a high percentage of inhibition of cell proliferation for the methanol extract of the stem bark EMC (80.11 ± 8.12%) and alkaloidal fraction of FCAF leaves (80.56 ± 8.15%) against the human hepatocellular carcinoma and for the mixture of compounds govanine, liriodenine and lysicamine (IC50 3.10 μg mL-1) against human promyelocytic leukemia (HL-60) which can be attributed to the presence of liriodenine. Most of the identified alkaloids are described in different species of Annonaceae, particularly in the Guatteria genus. Thus, it appears that G. pogonopus presents a caracteristic chemotaxonomy the Annonaceae family and, linked to this, is a promising source of substances with potential cytotoxic activity.